2019
DOI: 10.1002/pssb.201900117
|View full text |Cite
|
Sign up to set email alerts
|

A First Principle Study of Structural, Electronic, and Vibrational Properties of LuPdBi Half‐Heusler Alloy

Abstract: Half-Heusler alloys offer a variety of applications in the field of electronics and superconductors. They are suitable for the formation of thermoelectric materials and superconductors. Their stupendous applications arouse curiosity among many researchers. Therefore, in this paper, a systematic study of structural, electronic, and vibrational properties has been done using density functional theory and density functional perturbation theory. The structural properties such as lattice constant, bulk modulus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 32 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…The reported results (table 2) again confirmed that resultant compound is ductile in nature at all hydrostatic pressures. All the calculated elastic constants and mechanical properties are in well agreement with reported theoretical work [10] for pure LuPdBi compound. The value of Grüneisen parameter (γ) provides information about anharmonic interactions [25] and gives an indication about phonon scattering i.e.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…The reported results (table 2) again confirmed that resultant compound is ductile in nature at all hydrostatic pressures. All the calculated elastic constants and mechanical properties are in well agreement with reported theoretical work [10] for pure LuPdBi compound. The value of Grüneisen parameter (γ) provides information about anharmonic interactions [25] and gives an indication about phonon scattering i.e.…”
supporting
confidence: 86%
“…Here Lu atom is present at (0, 0, 0), Pd at (0.25, 0.25, 0.25) and Bi at (0.5, 0.5, 0.5) [10], as shown in figure 1. The lattice parameter of pure LuPdBi was optimized in the neighborhood of the experimental lattice parameter (6.63 Å), the optimized lattice parameter (6.65 Å) is found to be in good agreement with available experimental [8] and theoretical [10] data as listed in table 1. The structural optimization of LuPdBi is illustrated in supplementary information (figure S1 (available online at stacks.iop.org/PS/96/125702/mmedia)).…”
Section: Electronic Propertiesmentioning
confidence: 95%
See 2 more Smart Citations
“…There are several experimental and computational studies reported in publications on half-Heusler alloys [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Nevertheless, the search for viable half-Heusler semiconductors with suitable properties for specific applications is still needed because some of the already discovered materials have limitations that hinder their suitability for certain applications.…”
Section: Introductionmentioning
confidence: 99%